Réponses

2013-12-07T13:58:46+01:00
1) x²-4-(x+2)(3x-5)
   x²-4-(3x²-5x+6x-10)
   x²-4-3x²+5x-6x+10
   -2x²-x+6
2) x=1/2
 -2(1/2)²-1/2+6
-2(1/4)-1/2+6
 -2/4-1/2+6
 -1/2-1/2+6=-1+6=5
3) x²-4 = (x-2)(x+2)
x²-4-(x+2)(3x-5)
(x-2)(x+2)-(x+2)(3x-5)
(x+2)(x-2)-(3x-5)
(x+2)(x-2-3x+5)
(x+2)(-2x+3)
2013-12-07T14:02:28+01:00
1)
F = x^2 - 4 - (x + 2)(3x - 5)\\=x^2 - 4 - 3x^2 +5x - 6x + 10\\ = -2x^2-x+6

2)
F( \frac{1}{2} )=-2 (\frac{1}{2}) ^2- \frac{1}{2}+6 =  -\frac{1}{2} -  \frac{1}{2} +6 = -1 + 6 = 5

3)
x^2-4 = x^2 - 2^2 = (x-2)(x+2)\\F = x^2 - 4 - (x + 2)(3x - 5)\\F=(x-2)(x+2)- (x + 2)(3x - 5)\\F=(x + 2)(x-2-3x+5)\\F=(x+2)(-2x+3)

En espérant t'avoir aidé.